Aplicação exógena de artemisinina e indução floral em Artemisia annua L. - Marchese, J. A. [UNESP]; Broetto, F. [UNESP]; Ming, L. C. [UNESP]; Rehder, V. L G; Boaventura, S.; Vendramini, P. F.; Stefanini, M. B. [UNESP]; Guerreiro, C. P V [UNESP]; Leonardo, M. [UNESP] (My University, 2005)
The objective of this work was to evaluate the effect of different artemisinin concentrations in the flowering induction of A. annua. Two genotypes of A. annua (CPQBA 239x1V and 3MxPOP) were atomized with four different artemisinin concentrations (0, 500, 5000, and 10000 mg L-1). The application of artemisinin didn't induce the flowering of both genotypes tested, in none of the used concentrations.
External application of artemisinin in the induction of the flowering in Artemisia annua L.
Keywords: Growth and development; Medicinal plants; Photoperiodism; Phytohormones; Sweet wormwood; artemisinin; phytohormone; Artemisia annua; chemical structure; flowering; genotype; medicinal plant; nonhuman; photoperiodicity; plant development; plant growth; sweet wormwood